Efeito de doze semanas de treinamento resistido com suplementação de whey proteins e decanoato de nandrolona, sobre a expressão gênica de MTOR, MURF-1 e MAFBX em ratos wistar - XAVIER, Roger Medeiros (2019)
Aim: To verify the effect of 12 weeks of resistance training with Whey Proteins supplementation and Nandrolone Decanoate application for gene expression in MTOR pathways and MURF-1 and MAFBX protein degradation of the Wistar male gastrocnemius muscle. Materials and Methods: Was performed with 97 male Wistar rats with initial age of 60 days and body mass of 200g to 350g, randomly distributed in 11 groups. The protocol lasted 12 weeks with resistance training three times a week, daily supplementation, and application of Nandrolone Decanoate. The gene expression of MTOR, MURF-1 and MAFBx in the white portion of the gastrocnemius muscle was evaluated by the real time polymerase chain reaction (PCR-RT) method, histological analysis, and muscle strength every two weeks. Statistical analysis will consist of descriptive and analytical (Shapiro-Wilk (p> 0.05), Anova (p <0.05) and Tukey Posttest (p <0.05). Results: MTOR was higher and significant in the Resistance Control Training (TC) group compared to the Whey Proteins W2 (p = 0,0176), W4 (p = 0,0329) and W6 (p = 0,0437) and W6 supplemented groups. In the MURF-1 gene expression, the Control group (C) showed a significant difference in relation to the W4 (p = 0,0319) and W6 (p = 0,0160) groups. In the MAFBX gene expression there was no significant difference in the groups. Discussion: MTOR expression was significant in the Resistance Control Training (TC) group compared to sedentary supplements W2 (p = 0,0176), W4 (p = 0,0329) and W6 (p = 0,0437), along with MURF-1 expression that shows a difference in the control group (C) compared to the supplemented W4 (p = 0,0319) and W6 (p = 0.0160), despite the partially positive result, other groups with larger amounts of interventions showed no significant difference. Conclusion: The dose (0.5 mg / kg) does not to be sufficient to influence a gene expression of MTOR, MURF-1 and MAFBX.